The Features of The Works of Uzbek Family Scholar Abdurashid Munavvarov in The Development Of The Pedagogical System of Proper Organization Of Family Upbringing - Gullola Jumanazarova (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2024)
A person's unchanging value is his or her family. Throughout history, the family has had a special place in society. However, as the social order changes, ways to understanding family values evolve. The contemporary era of global information technology raises challenging problems for everyone involved in the process of teaching the next generation: how can young people be protected from the detrimental impact of aggressive propaganda promoting an immoral lifestyle? In this sense, Uzbek family scholar Abdurashid Munavvarov developed the principles of purposeful family upbringing, whose main purpose is the formation of a comprehensively spiritually developed, intellectually and morally mature person in the family. This article offers a critical analysis of the theories advanced within the framework of Abdurashid Munavvarov's writings and scientific investigations into in the development of the pedagogical system of proper organization of family upbringing.